2009
DOI: 10.1088/1751-8113/42/32/322002
|View full text |Cite
|
Sign up to set email alerts
|

Stretched polygons in a lattice tube

Abstract: We examine the topological entanglements of polygons confined to a lattice tube and under the influence of an external tensile force f. The existence of the limiting free energy for these so-called stretched polygons is proved and then, using transfer matrix arguments, a pattern theorem for stretched polygons is proved. Note that the tube constraint allows us to prove a pattern theorem for any arbitrary value of f, while without the tube constraint it has so far only been proved for large values of f. The stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…We next discuss some results about the likelihood of each type of pattern. There are known "pattern theorems" available for both the fixed-edge and fixed-span models studied here (see [3,4]), as well as for Hamiltonian polygons (see [7]). The theorems focus on proper polygon patterns (see [5] for more precise definitions) which include the proper knot patterns defined here.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…We next discuss some results about the likelihood of each type of pattern. There are known "pattern theorems" available for both the fixed-edge and fixed-span models studied here (see [3,4]), as well as for Hamiltonian polygons (see [7]). The theorems focus on proper polygon patterns (see [5] for more precise definitions) which include the proper knot patterns defined here.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…To the best of our knowledge there exist only * Electronic address: michelet@sissa.it † Electronic address: orlandini@pd.infn.it a limited number of experimental and numerical studied of the size and shape of DNA molecules in nanoslits [8,18,[31][32][33]. These seminal studies have addressed the interesting issue of whether multiple scaling regimes exist in linear DNA filaments inside slits.…”
Section: Introductionmentioning
confidence: 99%
“…This result, and that on the probability of knots, both indicate that the number of conformations of a certain height decreases more rapidly with deviation from the entropically favoured height, as knot complexity increases. The effect of applying a force to ring polymer molecules has also been investigated [10,11]. It is found that the force affects the probability of a non-trivial knot for finite chains, but that this probability still tends to unity in the infinite length limit.…”
mentioning
confidence: 99%